2021
DOI: 10.1097/bot.0000000000001901
|View full text |Cite
|
Sign up to set email alerts
|

External Fixator–Assisted Reduction of Distal Femur Fractures: A Technical Trick

Abstract: Restoration of anatomical alignment while preserving the soft-tissue envelope around the fracture site remains a challenge during distal femur fracture fixation. Although the lateral distal femoral locking plate allows surgeons to achieve adequate bony stability, their application has been associated with malalignment leading to inferior outcomes. We propose a biologically friendly, percutaneous technique that sequentially reduces and aligns distal femur fractures with an anterior external fixator before defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…External fixator-assisted reduction is a well-known technique in traumatology, several authors reported the use of external fixator to restore anatomical alignment and length before internal fixation. Shymon and co-workers [ 16 ] described a percutaneous technique that sequentially reduces and aligns distal femur fractures with an anterior external fixator before definitive fixation with a lateral distal femoral locking plate. Gopinathan and colleagues [ 3 ] proposed a Fixator Assisted Submuscular plating Technique (FAST), which minimizes the surgical time and simplifies the submuscular plating in pediatric femur fractures.…”
Section: Discussionmentioning
confidence: 99%
“…External fixator-assisted reduction is a well-known technique in traumatology, several authors reported the use of external fixator to restore anatomical alignment and length before internal fixation. Shymon and co-workers [ 16 ] described a percutaneous technique that sequentially reduces and aligns distal femur fractures with an anterior external fixator before definitive fixation with a lateral distal femoral locking plate. Gopinathan and colleagues [ 3 ] proposed a Fixator Assisted Submuscular plating Technique (FAST), which minimizes the surgical time and simplifies the submuscular plating in pediatric femur fractures.…”
Section: Discussionmentioning
confidence: 99%